A Novel Piezoelectric-Assisted Non-Surgical Periodontal Treatment: A Prospective Case Series - Roberto Rotundo; Lorenzo Marini; Mauro Carere; Cinzia Trezza; Giovanni Marras; Michele Nieri; Andrea Pilloni (MDPI AG, 2023)
The purpose of this study was to evaluate the clinical efficacy of a non-surgical periodontal treatment using a piezoelectric power-driven device with a novel insert. Plaque index (PlI), bleeding on probing (BoP), probing depth (PD), recession depth (Rec) and clinical attachment level (CAL) were assessed at 6 weeks, 3 months and 6 months. Furthermore, tooth mobility and furcation involvement were recorded and chewing discomfort and dental hypersensitivity were evaluated. Eighteen stage I to IV periodontitis patients providing 437 teeth and 2622 sites in total were analyzed. At six weeks, CAL gain (0.4; p < 0.0001), PD reduction (0.4; p < 0.0001) and Rec increase (0.1; p = 0.0029) were statistically significant. Similarly, the mean number of sites with PD > 4 mm and absence of BoP significantly decreased between baseline and 6 weeks (−12.7; p < 0.0001). At this time point, the patient's chewing discomfort was also significantly diminished (1.4; p = 0.0172). Conversely, no statistically significant changes were observed between 6 weeks and 3 months and between 3 months and 6 months for any of the clinical variables evaluated. In conclusion, within the limitation of this study, mechanical piezo-assisted non-surgical periodontal treatment in conjunction with an innovative tip resulted significantly efficacious to reduce pathological periodontal pockets, to gain clinical attachment and to reduce gingival inflammation.